Tumor-related Lipid Exudation and Associated Tumor-related Complications after Plaque Radiotherapy of Posterior Uveal Melanoma. Issue 3 (May 2013) - Mashayekhi, Arman; Tuncer, Samuray; Shields, Carol L.; Shields, Jerry A.
Purpose: To identify complications associated with tumor-related lipid exudation (TRLE) after plaque radiotherapy of posterior uveal melanoma. Methods: Comparative study including 294 patients with posterior uveal melanoma who developed TRLE after plaque radiotherapy (TRLE group) and 294 patients who did not develop TRLE (non-TRLE group). Patients in the TRLE group were matched with patients in the non-TRLE group for age, gender, and initial tumor thickness. Results: The TRLE group was associated with significantly higher incidence of postradiation complications including early transient increase of serous retinal detachment (p<0.001), iris neovascularization (NVI) (p<0.001), neovascular glaucoma (NVG) (p<0.001), posterior synechia (p<0.001), vitreous hemorrhage (p<0.001), subretinal hemorrhage (p<0.001), and retinoschisis (p<0.001). A significant relationship was found between extent of TRLE and NVI (p<0.001), NVG (p<0.001), posterior synechia (p = 0.007), and retinoschisis over tumor (p = 0.010). Radiation-induced retinopathy, maculopathy, and papillopathy were not associated with presence or extent of TRLE. Tumor-related lipid exudation was also associated with worse final visual acuity (p = 0.011), higher rate of secondary enucleation (p<0.001), and lower rate of systemic metastasis (p = 0.006). Conclusions: Tumor-related lipid exudation following plaque radiotherapy of posterior uveal melanoma is associated with major intraocular complications and portends poor prognosis for final visual acuity and eye retention. These findings provide evidence for the presence of 2 distinct pathogenic mechanisms, one radiation-induced and one tumor-related, in development of postradiation complications in eyes with posterior uveal melanoma.